Voluntary Servitude and Totalitarianism in Dystopian Novels of the 20th Century: Status of the Literature in Brave New World, 1984 and Fahrenheit 451 - Štahan, Matija (Poznańskie Studia Slawistyczne, 2019)
The article thematises the relationship of the will to rule and the will to be ruled in the aforementioned dystopian novels by Aldous Huxley, George Orwell and Ray Bradbury. The first part of the article points out Hannah Arendt’s observations on the nature of totalitarianism, the second part deals with the similarities concerning the status of literature in the fictitious totalitarian societies represented in the three novels, whereas the final part exemplifies Arendtʼs views through Étienne de La Boétieʼs writings on “voluntary servitude”. The conflict between those who want to be ruled and those who want to be free reflects the clash of those who want to annihilate literature and those who want to preserve it.